1999
DOI: 10.1111/j.1600-065x.1999.tb01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential strategies utilised by papillomavirus to evade host immunity

Abstract: The co-evolution of papillomaviruses (PV) and their mammalian hosts has produced mechanisms by which PV might avoid specific and non-specific host immune responses. Low level expression of PV proteins in infected basal epithelial cells, together with an absence of inflammation and of virus-induced cell lysis, restricts the opportunity for effective PV protein presentation to immunocytes by dendritic cells. Additionally, PV early proteins, by a range of mechanisms, may restrict the efficacy of antigen presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 72 publications
(1 reference statement)
2
73
0
1
Order By: Relevance
“…31 The immune system plays a decisive role in determining the clinical outcome of HPV disease, as demonstrated by the increased persistence and enhanced neoplastic progression of HPV infections in hosts with cell-mediated immune deficiencies. 32,33 However, even in immunocompetent individuals, HPVs persist for a significant period of time before activation of the host immune system.…”
Section: Discussionmentioning
confidence: 99%
“…31 The immune system plays a decisive role in determining the clinical outcome of HPV disease, as demonstrated by the increased persistence and enhanced neoplastic progression of HPV infections in hosts with cell-mediated immune deficiencies. 32,33 However, even in immunocompetent individuals, HPVs persist for a significant period of time before activation of the host immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of cytokines was based upon previous reports on their importance in HPV-associated cervical neoplasia (30,31) or their in vitro expression following DC exposure to HPV proteins (24,32). To determine the effect of HPV18 transfection on cytokine production, transfected DCs, non-transfected DCs and DCs transfected with empty vector were cultured to confluency.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor necrosis factor-α (TNF-α) interleukin-6 (IL-6), transforming growth factor-β (TGF-β) and monocyte chemotactic protein-1 (MCP-1) ELISA kits were purchased from Life Technologies. The selection of cytokines for this study was based upon published data suggesting their involvement in mechanisms controlling tumor growth or regression (14,30,(36)(37)(38). Transfected and non-transfected cells (10 6 cells/well) were placed in 12-well plates and grown to confluency and activated with lipopolysaccharide (1 µg/ml; LPS; Sigma Chemical Co., St. Louis, MO, USA).…”
Section: Rt-pcr Detection Of E6 and E7 Transcriptsmentioning
confidence: 99%
“…Over the last two decades, several studies have shown the use of IFN for treating cervical intraepithelial neoplasia (CIN) ( Byrne MA et al 1986;Choo YC et al 1986;Cinel A et al 1991;Di Roma E et al 2001;Dunham AM 1990;Frazer IH et al 1999;Frost L et al 1990;Grismondi GL et al 1995;Katesmark M et al 1999;Micheletti L et al 1992;Murta EF and Tavares Murta BM, 2004;Rotola A et al 1995;Schiffman MH, 1995;Sikorski M and Zrubek H, 2003). Physical methods are the ones most utilized for treating high-grade lesions.…”
Section: Lower Genital Tractmentioning
confidence: 99%